2019
DOI: 10.1021/jacs.9b06093
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Triggered Formation of a Peroxo-Fe2(III/III) Intermediate during Fatty Acid Decarboxylation by UndA

Abstract: The iron-dependent oxidase UndA cleaves one C3–H bond and the C1–C2 bond of dodecanoic acid to produce 1-undecene and CO2. A published X-ray crystal structure showed that UndA has a heme-oxygenase-like fold, thus associating it with a structural superfamily that includes known and postulated non-heme diiron proteins, but revealed only a single iron ion in the active site. Mechanisms proposed for initiation of decarboxylation by cleavage of the C3–H bond using a monoiron cofactor to activate O2 necessarily invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
129
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(145 citation statements)
references
References 32 publications
15
129
0
1
Order By: Relevance
“…As in Fe 2 (II/II)-SznF, core a3 of CADD, which we presume to have been characterized in its oxidized Fe 2 (III/III) state, is fully a-helical in the published structure. By contrast, UndA shares with SznF the property of cofactor instability and still has not been crystallographically characterized with its diiron cluster intact, despite concerted efforts toward this goal (43). Core a3 in the UndA structure is partially disordered, as in the previously reported structures of SznF (37), and the Asp315 equivalent, Asp198, resides in or near this unmodeled stretch (Fig.…”
Section: Role Of Core A3 Dynamics In Cofactor Instability Of Hdosmentioning
confidence: 76%
See 4 more Smart Citations
“…As in Fe 2 (II/II)-SznF, core a3 of CADD, which we presume to have been characterized in its oxidized Fe 2 (III/III) state, is fully a-helical in the published structure. By contrast, UndA shares with SznF the property of cofactor instability and still has not been crystallographically characterized with its diiron cluster intact, despite concerted efforts toward this goal (43). Core a3 in the UndA structure is partially disordered, as in the previously reported structures of SznF (37), and the Asp315 equivalent, Asp198, resides in or near this unmodeled stretch (Fig.…”
Section: Role Of Core A3 Dynamics In Cofactor Instability Of Hdosmentioning
confidence: 76%
“…within the relatively open HDO core, and it was initially suggested that UndA uses the observed monoiron(II) center for O 2 activation (41). A pair of later studies showed, by contrast, that the iron cofactor is dinuclear (42,43). One of these studies characterized a µ-peroxo-Fe 2 (III/III) complex on the reaction pathway (43).…”
Section: Significance Statementmentioning
confidence: 99%
See 3 more Smart Citations